Two‐Dimensional Reconstruction of Ionospheric Plasma Density Variations Using Swarm. Issue 6 (3rd June 2020) - Fæhn Follestad, A.; Clausen, L. B. N.; Miloch, W. J.; van den IJssel, J.; Haagmans, R.
Abstract: Space weather phenomena such as scintillations of Global Navigation Satellite Systems (GNSS) signals are of increasing importance for aviation, the maritime, and civil engineering industries. The ionospheric plasma irregularities causing scintillations are associated with strong gradients in ionospheric plasma density. To provide nowcasts and forecasts of space weather effects, it is vital to monitor the ionosphere and detect strong density variations. To reconstruct plasma density variations in the polar cap ionosphere, we use total electron content (TEC) estimates from the Swarm satellites' GPS receivers. By considering events where the Swarm satellites are in close proximity, we obtain plasma density variations by inverting TEC measurements on a two‐dimensional grid. We first demonstrate the method using synthetic test data, before applying it to real data. The method is validated using in situ Langmuir probe measurements and ground‐based TEC observations. We find that the new method can reproduce density variations, although it is sensitive to the geometry of the Swarm satellite constellation and to the calculated plasma temperature. Our proposed method opens new possibilities for ionospheric plasma monitoring that uses GPS receivers aboard low Earth orbit (LEO) satellites. Key Points: We present a new method for reconstructing 2‐D plasma density variations using GPS TEC from the Swarm satellites The results agree well with Langmuir probe density measurements and ground‐based TEC observations The method allows for monitoring plasma density in the ionosphere using satellites in low Earth orbit